Complexidade e avaliação da confiabilidade da informação na Internet - Valencia, José Roberto Amaya (2019)
The present research aims to show the strategies that the students of the PostGraduation Program in Linguistics of the Federal University of Ceará (UFC) use to evaluate the reliability of the information on health topics conveyed on the Internet. Based on the concept of Digital Literacy and the New Literacies Perspective of Online Reading Comprehension (LEU et al., 2013), the informants' online research process will be studied in the light of Complexity Theory, specifically from the approaches of reading as a Complex Adaptive System, proposed by Coiro and Coscarelli (2010) and Franco (2011), to analyze the processes that interact simultaneously and dynamically in online reading comprehension. In order to do this, we chose as analytical categories: prior knowledge (ALEXANDER, 1994; COIRO, DOBLER, 2007), self-explanation and monitoring (GOLDMAN et al., 2012); which, by interacting dynamically with each other, give rise to strategies for evaluating the reliability of information on the Internet. To look at these interactions, we ask for 7 students of the Postgraduate Program in Linguistics of the Federal University of Ceará (UFC) to search the internet for an open-ended question on a controversial topic (vaccines and autism). With the support of Hypercam 4 software and making use of the Verbal Protocol (LOPES, 2009), informants' navigational paths were recorded in audio and video. Soon after the analysis of the data collected, the results revealed that, although evidence was registered that supports the idea that the strategies for assessing information reliability arise from the interaction of prior knowledge, self-explanation and monitoring, it can not be said with certainty, that these results are always the product of these relations; and that it sometimes seems that the criteria and tools for evaluating information are learned and applied automatically.